Navigating Idioms Processing in Bilinguals: : A Systematic Literature Review - Paramarta, Bagus Pragnya; Irmawati, Mila (Language Horizon: Journal of Language Studies, 2025)
An idiom is an instance of metaphor with a specific form and figurative meaning. To interpret the meaning behind the literal meaning of the idiom, we need to perform a specific processing strategy to help us understand the concept and meaning of a certain idiom. Many studies have examined the idiom processing in monolinguals and bilinguals. Particularly in bilinguals, idiom processing requires a certain complex process since there will be a competition and influence from L1 to L2 and vice versa. Semantic processing strategy differences between L1 and L2 also play a crucial role in the idiom cognitive processing and comprehension. In terms of processing, both offline and online processing research have been documented to better understand the idiom processing in monolinguals and bilinguals. Since the fast-changing research on bilinguals, the present study aims to navigate the idioms processing in bilingual research to shed light on the current trend and development in such studies. By implementing a systematic literature review using the PRISMA Flow Diagram, the current study shows that the current condition of bilingual idiom comprehension involves a finely tuned balance between analytical processing and automatic retrieval, where moderated by cross-language interference and cognitive control. The results depict that from 11.100 studies on language processing, there are 999 have focused on idiom language processing, and only 100 have been reported in studies from 2000-2025. Moreover, 26 research reports were assessed for eligibility due to having focused on idiom processing in bilinguals, and finally, 16 studies were included in the review. The majority of studies on idiom processing have discussed how bilinguals have a positive effect on idiom processing. While there are still some open questions remain open, future research needs to be done to gain more empirical evidence of idiom processing in bilinguals.